STUDI TENTANG PEMBUATAN 1-(3,4-METILENDIOKSIFENIL)- 2-PROPILALKOHOL - Fatimah, Feti (Sam Ratulangi University, 2009)
A study has been carried out to synthesis of 1-(3,4-methylenediooxyphenil)-2-propylalcohol from safrole. Thesynthesize was done using react the oxymercuration-demercuration by means of mercury of acetate andsodium of boronhydride, while identifying conducted with the liquid gas chromatography and spectrometer.The experimental result show that the percentage yield of 1-(3,4-methylenedioxyphenil)-2-propylalcohol was77,78%.Â Keywords: 1-(3,4-methylenedioxyphenil)-2-propylalcohol